Upcycling end-of-life carbon fiber in high-performance CFRP composites by the material extrusion additive manufacturing process - Ateeq, Muhammad; Nazir, Aamer (Frontiers in Mechanical Engineering, 2024)
Each year, a significant amount of waste is produced from carbon fiber polymer composites at the end of its lifecycle due to extensive use across various applications. Utilizing regenerative carbon fiber as a feedstock material offers a promising and sustainable approach to additive manufacturing based on materials. This study proposes the additive manufacturing of recycled carbon fiber with a polyamide-12 polymer composite. Filaments of recycled carbon fiber-reinforced polyamide-12 (rCF-PA12) with different recycled carbon fiber contents (0%, 10%, and 15% by weight) in the polyamide-12 matrix are developed. These filaments are utilized for 3D printing of specimens by using various infill density parameters (80% and 100%) on a fused deposition modeling 3D printer. The study examined how the fiber content and infill densities influenced the flexural performance of the printed specimens. Notably, the part containing 15 wt% recycled carbon fiber (rCF) composites showed a significant improvement in flexural performance due to enhanced interface bonding and effective fiber alignment. The results indicated that reinforcing the printed part with 10% and 15 wt% recycled carbon fiber (rCF) improved the flexural properties by 49.86% and 91.75%, respectively, compared to the unreinforced printed part under the same infill density and printing parameters. The investigation demonstrates that the additive manufacturing-based technique presents a potential approach to use carbon fiber-reinforced polymers waste and manufacture high-performance engineering, economic, and environmentally friendly industrial applications with the complicated design using different polymer matrices.